Optimizing alginate extraction using Box-Behnken design: Improving yield and antioxidant properties through ultrasound-assisted citric acid extraction - Chica, Letícia Rustici [UNESP]; Yamashita, Camila [UNESP]; Nunes, Natalie Stephanie Sawada [UNESP]; Negreiros, Arthur Torres [UNESP]; Moraes, Izabel Cristina Freitas; Ferreira, Antônio Gilberto; Mayer, Cassia Roberta Malacrida [UNESP]; Haminiuk, Charles Windson Isidoro; Branco, Ciro Cesar Zanini [UNESP]; Branco, Ivanise Guilherme [UNESP] (Elsevier, 2024)
The Box-Behnken Design was employed to optimize the extraction of alginate (ALG) from Sargassum cymosum C. Agardh using ultrasound-assisted treatment and substituting hydrochloric acid with citric acid during the acidic step. The study aimed to maximize yield and enhance the functional properties of the polysaccharide. The effects of pH of the citric acid (CA) solution, ultrasound power, and treatment time were evaluated in terms of yield, viscosity-average molecular weight (Mw), dynamic viscosity (µdyn), and antioxidant capacity (AC) of the ALG. The optimized conditions (176 W, 15 min, pH 1) resulted in a yield of 54.20 %, Mw of 202.56 kDa, µdyn of 10.43 mPa•s, and AC of 80.81 µM Trolox g-1. The lowest pH was found to be optimal for enhancing alginate extraction efficiency and improving its properties (viscosity and antioxidant capacity). Under optimized conditions, the CA solution resulted in a higher ALG yield with minimal changes in Mw and µdyn, while also retaining the main functional groups and chemical bonds, and doubling the AC compared to hydrochloric acid. The results indicate that ultrasound-assisted extraction is a promising method for extracting alginate from brown algae and that CA can satisfactorily replace the conventional solvent used in the acidic treatment.
Keywords: Alginate; Physicochemical properties; Quality; Sargassum; Seaweed